An assessment of the impact of disaster risks on dairy supply chain performance in Zimbabwe - Felix Chari; Bethuel Sibongiseni Ngcamu (Cogent Engineering, 2017)
This study investigated the impact of disaster risks on the performance of Zimbabwe’s dairy supply chains. The study was initiated on the premise that Zimbabwe is at high risk and is highly vulnerable to disasters such as drought, cyclones, floods, animal diseases, and crop pests. This study employed a mixed method approach that involved the use of structured questionnaires, semi-structured interviews and observations. A combined total of 92 dairy farmers and milk processors were sampled from a target population of 122 from major milk producing regions in the country, with a response rate of 85%. Key informants, comprising 18 dairy authorities and 30 retailers were purposively sampled. Chipinge, Mutare, Harare, Gweru, and Bulawayo, were the regions under investigation, covering the greater part of the country. The findings computed through Ordinary Least Square regression analysis, indicated that an overall index of disaster risks impacted negatively on dairy supply chain performance. Major indicators of the disaster impacts were job losses, food insecurity, reduced milk productivity, and the general retarded growth in dairy businesses. The results were also corroborated by outcome of interviews with key informants. This study recommends that both the private sector and the government should invest in disaster reduction strategies, to enhance the effective and sustainable performance of dairy supply chains in Zimbabwe. The findings from the study contribute to literature on disaster risks, which has largely been under-explored in developing countries, will also assist practicing managers, particularly in dairy sector, in dealing with disaster risk issues. Similarly, the study findings will assist policy makers to consider enacting policies, and improve existing ones, to assist communities faced with disaster risks.